Reaktualisasi Pendidikan Islam Multikultural Perspektif Abdul Munir Mulkhan - Mustamar Iqbal; Moh In’ami; Afaf Afaf (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2023)
The cultural, ethnic, and religious diversity that characterises Indonesian society can often be a source of social friction if it is not balanced with inclusive and transformative education. Islamic education, as one of the dominant education systems in Indonesia, is still often trapped in a normative-doctrinal approach that lacks multicultural awareness. This article aims to examine Abdul Munir Mulkhan's thought as a conceptual offering in the reactualization of multicultural Islamic education that is more contextual and transformative. This research uses a qualitative approach to library research by examining the primary and secondary works of Abdul Munir Mulkhan and other relevant supporting literature. The results of the study show that Mulkhan offers a model of Islamic education based on transformative humanism and substantive multiculturalism through the concept of